PENGEMBAGANGAN MEDIA KARTU GAMBAR BERBANTUAN TEKNIK SCRAMBEL DALAM MEMBACA PERMULAAN SISWA KELAS III SDN 5 DANGER TAHUN AJARAN 2022/2023 - Miskan Yunanda; I Nyoman Karma; Moh. Irawan Zain (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2023)
The background of this research is to present the students who have not read optimally yet because of media that can not support students' problems. the purpose of this study is to produce in the form of media, namely the development of picture card media assisted by the Scrambel Technique in the reading material of beginning grade III students of SDN 5 Danger in the 2022/2023 school year. This type of research is development research. The subjects in this study were third-grade students totaling 9 people with small groups of 3 members and SDN 5 Danger class teachers. The methods used in data collection are interview methods, questionnaire sheets, and documentation. The data analysis technique was carried out using a Likert scale to get a score with the assessment score used, namely 1-4. The results in this study are picture card learning media assisted by scramble techniques in beginning reading developed using the ADDIE model which consists of several research stages, namely analysis, design, development, implementation, and evaluation. In addition, the picture card media assisted by the scramble technique in beginning reading is declared effective with a percentage value of 72.5% with a good or effective category to use. The percentage of material expert validation obtained a percentage value of 90% with a very good or very effective variety to use.